Multi-ciphertext batch auditable decryption outsourcing SM9-HIBE key encapsulation mechanism - Kuan LIU; Jianting NING; Wei WU; Shengmin XU; Chao LIN (Tongxin xuebao)
The decryption operation of SM9-HIBE key encapsulation mechanism required two bilinear pairing operations, for the equipment requiring frequent decryption of massive data and with limited computing resources, such resourcing-consuming pairing operation will become an important bottleneck restricting the system deployment.To address the above issue, a decryption outsourcing key encapsulation mechanism OASM9-HIBE based on SM9-HIBE was proposed, which supported multi-ciphertext batch auditing.The Fujisaki-Okamoto transformation technology was utilized to prove the RCCA security of OASM9-HIBE under the random oracle model.All resourcing-consuming bilinear pairing operations were safely offloaded to the cloud server in OASM9-HIBE, the k-th hierarchical user only need to perform one simple exponentiation operation to complete the final decryption.The decryption efficiency of the original SM9-HIBE was effectively improved under the premise of not changing the downward proxy generation function of the user’s private key between hierarchical.OASM9-HIBE additively achieved the property of batch auditing of multi-transformed ciphertexts by employing the key blinding technology.Theoretical analysis and evaluation of experimental data highlight the feasibility and efficiency of OASM9-HIBE, OASM9-HIBE extends the application field of SM9 series algorithms.